دراسة بعض الخصائص الفيزيائيه والكيميائيه لرواسب بعض مواقع نهر الفرات في مدينة محافظة الناصريه - اسماعيل محمد (University of Thi-Qar Journal of Science, 2010)
The physical and chemical characteristics of sediment for the Euphrates river were studied in four locations alongside the river in the southern part of Al Nassiria city .The stations were chosen according to pollution probability. The investigated characteristics include pH values for the studied locations were between (9.98.9).The highvalueof conductivity in the sediment was 1844 µs/cm and the lowest was 1360 µS/cm. The alkalinity of sediments ranged between(166-237) mg/l, calcium, magnesium, chloride, phosphate, nitrate,sulfate,sodium, andpotassium values for the sediment ranged between (160-303) (104-182) (44- 93) (3.1-6.7) (3347) (82-164) (48-115) (36-77) mg/l respectively.